COVID-19 Caregiving Avalanche: The Impact on Emotional Exhaustion on Female Natural Science and Engineering Academics - Vadnais, Arlana J.; Peter, Tracey; Dengate, Jennifer; Farenhorst, Annemieke; Mavriplis, Catherine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2024)
Gender disparity persists in the personal caregiving of children and older adults, and in professional caregiving duties, with many workplace policies and cultures favoring the “ideal worker” and presenting significant and continuing barriers to female caregivers’ professional success and well-being. The recent pandemic both highlighted and augmented this disparity as schools, daycares, and adult care facilities closed or implemented restrictions. This study interprets results from the July 2021 Canadian Natural Sciences & Engineering (NSE) Faculty Workplace Climate Survey by empirically assessing the impact on emotional exhaustion of the increased caregiving burden during the COVID-19 pandemic on female academics in the highly masculinized NSE fields. Results indicate that women were more likely to experience emotional exhaustion even when other factors were considered. Collegiality and inclusion were found to be protective factors, illustrating important implications for, and the retention and support of, success and well-being of female NSE academics.